Revealing the Organizational Nexus: Culture, Support, Citizenship, and Performance: Membeberkan Nexus: Budaya Organisasi, Dukungan, Kewarganegaraan, dan Kinerja - Putri Rizkika Aida; Rifdah Abadiyah (Universitas Muhammadiyah Sidoarjo, 2022)
This quantitative study investigated the interplay between organizational culture, perceived organizational support (POS), organizational citizenship behavior (OCB), and employee performance. The research, conducted at a logistics technology company, examined a sample of 75 employees through a Likert scale-based questionnaire. Path analysis using SmartPLS 3 for Windows was employed for data analysis. The findings revealed significant relationships between the variables. Organizational culture and POS had direct positive impacts on employee performance, while OCB acted as a mediator between organizational culture and employee performance. The results contribute to understanding the factors influencing employee performance and emphasize the significance of fostering a supportive organizational culture and enhancing perceived support to promote desirable workplace behaviors. These findings provide valuable insights for practitioners and managers aiming to improve organizational effectiveness and productivity. Highlights: The study examines the impact of organizational culture and perceived organizational support on employee performance, with a focus on the role of organizational citizenship behavior. The research adopts a quantitative approach, utilizing questionnaires and path analysis techniques to analyze data collected from 75 employees. The findings demonstrate significant relationships between organizational culture, perceived organizational support, organizational citizenship behavior, and employee performance, providing valuable insights for enhancing workplace effectiveness and productivity. Keywords: Organizational culture, Perceived organizational support, Employee performance, Organizational citizenship behavior (OCB), Quantitative research.